Much ado about vampires eaudiobook Dark ones (macalister) series, book 9. - MacAlister, Katie (Dark Ones, 2011)
Katie MacAlister's sultry paranormal romances zip to the top of best-seller lists across the globe. Here, Corazon Ferreira discovers she was the mate of a gorgeous vampire in a previous life. But despite the lingering attraction Corazon feels, the image of the vampire killing a victim just won't leave her mind. Only when her life depends on him does she finally decide to ignore her head and listen to her heart.